The Meaning of News Photos of the Islamic Defensive Action 411 and 212 in Harian Waspada - Topan Bilardo; Suwardi Lubis; Syukur Kholil (Budapest International Research and Critics University, 2019)
The development of photography both directly and indirectly is in line with the development of the journalistic field. Digital technology that is growing rapidly at this time also provides a significant contribution. Photos that record an event can be immediately disseminated in seconds using digital cameras and computer devices that have internet facilities. the photos that analyzed the meaning of photo denotations that appear such as mass mobilization, burning actions due to clashes between the masses and the police as well as photos of the Jakarta Governor's trial non-active Basuki Tjahja Purnama or Ahok reinforces the narrative that delivers news showing the two daily newspaper media giving support or partisanship to the actions of defending Islam 411 and 212. The meaning of connotations that appear in photographs can be seen from the photo taking process which generally from the upper and front sides of the object gives an impression of object density in the resulting image, further reinforcing the assumption of daily media alignment who only saw the Defensive Action of Islam 411 and 212 as a news commodity not a movement that defended the banners of Islam or defended a suspect in the religion, namely Basuki Tjahja Purnama or Ahok.